2019
DOI: 10.1063/1.5110265
|View full text |Cite
|
Sign up to set email alerts
|

Lagrangian statistics of pressure fluctuation events in homogeneous isotropic turbulence

Abstract: Homogeneous and isotropic turbulent fields obtained from two Direct Numerical Simulation databases (with Re λ equal to 150 and 418) were seeded with point particles that moved with the local fluid velocity to obtain Lagrangian pressure histories. Motivated by cavitation inception modeling, the statistics of events in which such particles undergo low-pressure fluctuations were computed, parameterized by the amplitude of the fluctuations and by their duration. The main results are the average frequencies of thes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…In contrast, for isotropic turbulence, the PDFs are non-symmetric with longer negative tails, which increase with Reynolds number (Bappy et al. 2019). The pressures are lower inside the QSVs, with similar shifts for both velocities, generally scaling with U 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, for isotropic turbulence, the PDFs are non-symmetric with longer negative tails, which increase with Reynolds number (Bappy et al. 2019). The pressures are lower inside the QSVs, with similar shifts for both velocities, generally scaling with U 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Hence, numerical simulations have been the primary source of information on the pressure in the core of eddies, although limited in Reynolds numbers. Recent studies aimed at understanding inception using Lagrangian pressure statistics following fluid elements or micro-bubbles have been performed for isotropic turbulence based on DNS data (Bappy, Carrica & Buscaglia 2019; Bappy et al. 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Numerical investigations of the particle concentration in turbulence solve the Navier-Stokes equation and use the Eulerian velocity field u(x, t) to evolve the trajectories of tracers x(t), integrating the transport equation. For particles with inertia, drag and other force terms such as gravity appears in the computation [4]. The evolution of large-scale supercomputers in combination with efficient algorithms has enabled numerical simulations of turbulent flow and transport of millions of particles.…”
Section: Numerical Studiesmentioning
confidence: 99%
“…Bappy et al conducted several numerical studies on the Lagrangian transport of tracers and finite sized bubbles in homogeneous isotropic turbulence [33]- [35]. Comparing Reλ of 150 to 418, they have found that for tracer particles higher concentrations are observed at higher Taylor microscale Reynolds numbers [4]. Their subsequent studies were concerned with preferential concentrations of finite-sized bubbles in lowpressure regions of flow concerned with cavitation inception.…”
Section: Numerical Studiesmentioning
confidence: 99%
See 1 more Smart Citation